Career Planning and Maintaining Well-being in Academic Plastic Surgery - Katie Egan, MD; Zain Aryanpour, MD; George Kokosis, MD; Lambros K. Viennas, MD, FACS (Plastic and Reconstructive Surgery, Global Open)
Summary:. Success in academic plastic surgery is based on the traditional pillars of promotion: clinical excellence, teaching, research, leadership, and service to the university and community. The time commitment and workload for career advancement are highly demanding and, therefore, well-being is essential to avoid burnout. A congruent healthy work environment that meets institutional goals and surgeons’ objectives can be established through inclusive, transparent, strategic, and operational planning. In this Special Topic article, we will review the requisites and challenges to promotion in academic plastic surgery and will discuss longitudinal strategies for well-being during the early, middle, and late academic career.